2010
DOI: 10.1101/gad.585310
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Holliday junction resolution by the human GEN1 protein

Abstract: Holliday junction (HJ) resolution is essential for chromosome segregation at meiosis and the repair of stalled/collapsed replication forks in mitotic cells. All organisms possess nucleases that promote HJ resolution by the introduction of symmetrically related nicks in two strands at, or close to, the junction point. GEN1, a member of the Rad2/XPG nuclease family, was isolated recently from human cells and shown to promote HJ resolution in vitro and in vivo. Here, we provide the first biochemical/structural ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
170
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 138 publications
(188 citation statements)
references
References 77 publications
18
170
0
Order By: Relevance
“…The evidence for diagonal digestion of cruciform DNA suggested that the resolution activity for Hollidayjunction structures in mammalian cells 28 could participate in this reaction. MUS81 nuclease, GEN1 and a complex of SLX4-SLX1 have been proposed as candidates for such a resolvase in mammalian cells [29][30][31][32][33][34][35][36][37] . To identify the cruciform resolvase working in this system, we performed siRNA screening coupled with monitoring the level of diagonal cleavage of the …”
Section: Resultsmentioning
confidence: 99%
“…The evidence for diagonal digestion of cruciform DNA suggested that the resolution activity for Hollidayjunction structures in mammalian cells 28 could participate in this reaction. MUS81 nuclease, GEN1 and a complex of SLX4-SLX1 have been proposed as candidates for such a resolvase in mammalian cells [29][30][31][32][33][34][35][36][37] . To identify the cruciform resolvase working in this system, we performed siRNA screening coupled with monitoring the level of diagonal cleavage of the …”
Section: Resultsmentioning
confidence: 99%
“…These include enzymes that catalyze structure-specific reactions of an apparently disparate group of nucleic acid substrates including DNA bubbles (xeroderma pigmentosum complementation group G (XPG)) (35), four-way junctions (GEN-1 (xeroderma pigmentosum complementation group G-like gap endonuclease, a putative human Holliday junction resolvase)) (36), as well as flapped, nicked, and 3Ј-overhang DNAs (FEN and EXO1) (2,20,37,38). Because all of these enzymes carry out the same chemical transformation, like T5FEN, they too will require two ions to effect phosphate diester hydrolysis.…”
Section: Discussionmentioning
confidence: 99%
“…It will be interesting to further dissect how GEN-1 affects DNA damage signalling. The biochemical activity of the mammalian GEN1 resolvase has been extensively characterized (Rass et al 2010 ) . At present no checkpoint function of mammalian GEN1 or yeast YEN1 was reported, and its Fig.…”
Section: Upstream Dna Damage Checkpoint Signalling In the C Elegans mentioning
confidence: 99%